2020
DOI: 10.1038/s41598-020-63923-7
|View full text |Cite
|
Sign up to set email alerts
|

Breaking conversational rules matters to captive gorillas: A playback experiment

Abstract: Across human cultures, conversations are regulated by temporal and social rules. The universality of conversational rules suggests possible biological bases and encourages comparisons with the communicative interactions of nonhuman animals. Unexpectedly, few studies have focused on other great apes despite evidence of proto-conversational rules in monkeys, thus preventing researchers from drawing conclusions on potential evolutionary origins of this behaviour. A previous study showed however that western lowla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Essentially, human conversation serves as a matrix for understanding the distribution of vocal communication between individual animals. Such rule-governed organizational properties have been reported in the vocal interactions of primates (Masataka, 2003), meerkats (Demartsev et al, 2018), bonobos (Levrero et al, 2019, and gorillas (Pougnault et al, 2020), as well as in birds (Henry et al, 2015). In particular, 9 these studies report phenomena of overlap avoidance and interlocutor selectivity rules (Levrero et al, 2019).…”
Section: The Conversational Modelmentioning
confidence: 71%
See 1 more Smart Citation
“…Essentially, human conversation serves as a matrix for understanding the distribution of vocal communication between individual animals. Such rule-governed organizational properties have been reported in the vocal interactions of primates (Masataka, 2003), meerkats (Demartsev et al, 2018), bonobos (Levrero et al, 2019, and gorillas (Pougnault et al, 2020), as well as in birds (Henry et al, 2015). In particular, 9 these studies report phenomena of overlap avoidance and interlocutor selectivity rules (Levrero et al, 2019).…”
Section: The Conversational Modelmentioning
confidence: 71%
“…Although counter‐intuitively (for it only dealt with the properties of human unique capacity of articulate verbal language), this notion has recently been brought, and appropriated, by the field of animal communication. The existence of rule‐governed conversation‐like mechanisms has since been investigated in a vast array of animal species: in birds and nonhuman primates, of course, but also in many mammals such as elephants, whales, dolphins and bats (see Pougnault, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we considered only those studies that involved individuals observing and reacting to turn-taking interactions of other interactants. Miller et al, 2004;Méndez-Cárdenas and Zimmermann, 2009;Morisaka et al, 2013;Terleph et al, 2018; see Figure 1), the field is strongly biased toward investigations involving primates (e.g., Rossano, 2013;Takahashi et al, 2013;Fröhlich et al, 2016c;Snowdon, 2017;Pougnault et al, 2020). Furthermore, Vanderhoff and Bernal Hoverud (2022) recently provided an overview of communicative exchanges in non-primate mammals with a special focus on antiphonal calling, duetting, and counter-singing (for definitions of terms, see Box 1) and showed that some singing species also possess turn-taking abilities.…”
Section: Turn-taking Comprehensionmentioning
confidence: 99%
“…Number of studies indexed in the Scopus and Web of Science databases that included the terms "duet" or "turn-taking" or "antiphonal calling" combined with the words "animal" or "non-human" or "Animalia" or "fauna" across years ( -). Overall, specific temporal relationships in turn-taking interactions have been found in a variety of non-mammal taxa including amphibians, birds, and insects (see for a recent review Pika et al, 2018;Pougnault et al, 2020;de Reus et al, 2021). Pika et al (2018), however, concluded that considerable methodological confounds and the employment of different terminologies in the existing studies (e.g., antiphonal calling and duetting) have significantly hampered insightful comparisons across species and an in-depth understanding of turn-taking complexity.…”
Section: Figurementioning
confidence: 99%
“…it is rarely shorter than the mean duration of a call, although most published maximum response delays appear slightly shorter in monkeys (around 1 or 1.5 s). Recent playback experiments using violation‐of‐expectations on gorillas and bonobos revealed that individuals could perceive whether a short silent gap between vocalisations produced by different interlocutors is present (Levréro et al ., 2017; Pougnault et al ., 2020). These results suggest that the presence of a response delay matters to the audience (Levréro et al ., 2017; Pougnault et al ., 2020).…”
Section: Testing the Social Complexity Hypothesis For Communication I...mentioning
confidence: 99%